fructificación del hongo ECM comestible Amanita ponderosa Malençon & R. Heim durante seis años consecutivos en un encinar adehesado de la Sierra - Daza, A.; Camacho, M. (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
Number and location of Amanita ponderosa Malençon & R. Heim sporocarps was followed through six years in a 3 ha holm-oak forest located in the Sierra de Aracena y Picos de Aroche Natural Park (Huelva), at the Southwest of Spain. The data indicated that patches of sporocarp production showed a very similar shape each year, but some spots showed differences seeming crop alternance or mast years. This species only fructifies in spring, being the fruiting period from 6 to 8 weeks, what coincides with the increasing of air-temperature from mid February to April. Differences in fruiting period length and total sporocarp production are related to rainfall and temperature. Results suggest that rainfalls at the end of summer and early autumn are crucial for the next spring fruiting, but rainfalls during fruiting period seem to have less influence in sporocarp production. During the sporocarp production period, it was related to soil temperature.
Keywords: gurumelo; mushroom harvest; raining; Soil temperature; sporocarp production and location

Efecto de la inoculación de cuatro bacterias promotoras del crecimiento vegetal sobre parámetros biométricos aéreos de plántulas de QUERCUS ILEX SSP.BALLOTA B. - Ramos, B.; Lucas García, J. A.; Santamaría, C.; Camacho, M.; Daza, A.; García, J. A. Lucas (III Congreso Forestal Español Congreso, 2001)
In the present work has studied the effect of four plant growth-promoting rhizobacteria (PGPRs) on growth of holm-oak plants (Quercus ilex ssp. ballota) in nursery before transplanting. The four strains assayed show in vitro metabolic capacities related with their action PGPR. All strains were able to increase significantly some parameters studied (high, diameter neck and dry weight). However, in the first sampling time (T1) only the strains Aur 6 and Aur 9 increased the high of the plants. In the last sampling time (T3) all strains increased the high, only Aur 6 increased the diameter neck and Cell 3, Aur 6 and Aur 9 increased the dry weight. It is important to point out that Aur 6 and Aur 9 increased the high and also the dry weight, this show that these strains enhance the general metabolism of the plants and also enhance the nutritional capacity and as a result the plants are more robust and with a better adaptative capacity.
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso issue: 1 pub-location: Granada
Keywords: adaptative capacity; colonization; PGPR; Quercus ilex ssp. ballota